2019
DOI: 10.1080/21691401.2019.1641509
|View full text |Cite
|
Sign up to set email alerts
|

Cinnamon attenuates adiposity and affects the expression of metabolic genes in Diet-Induced obesity model of zebrafish

Abstract: The prevalence of obesity is increasing at an alarming rate worldwide with about 30% of the world population classified as obese. Obese body structure results when energy intake exceeds energy expenditure in an individual. Increase in the consumption of high-energy eatables, in the context of portion and energy provided, has resulted in obese populations which is becoming the leading cause of metabolic disorders related to morbidity. The obesity-related comorbidity is an enormous liability on health services a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 54 publications
0
9
0
6
Order By: Relevance
“…Overfed zebrafish appear as an appropriate model to test the effects of some compounds on weight gain and its complications 15 , 39 , 40 . A. borbonica was selected as an interesting candidate given its potential or demonstrated anti-oxidant, anti-inflammatory, and anti-diabetic according to its traditional use and to in vitro studies 29 , 32 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Overfed zebrafish appear as an appropriate model to test the effects of some compounds on weight gain and its complications 15 , 39 , 40 . A. borbonica was selected as an interesting candidate given its potential or demonstrated anti-oxidant, anti-inflammatory, and anti-diabetic according to its traditional use and to in vitro studies 29 , 32 , 33 .…”
Section: Resultsmentioning
confidence: 99%
“…Metode lain yaitu menggunakan zebrafish jantan atau betina dengan dibagi menjadi 3 kelompok perlakuan [40,41], dan setiap kelompok perlakuan diberi makan 4 mg artemia/zebrafish [40], sedangkan menurut Kaur et al, kelompok perlakuan 1 dan 2 sama seperti menurut Zang et al, [38] namun yang membedakan pada kelompok perlakuan 3, yaitu zebrafish diinduksi dengan diberi makan berlebih artemia sebanyak 60 mg dengan dibagi 20 mg tiga kali dan ditambah 2 mg bubuk kayu manis tiga kali sehari dengan pemberian bubuk kayu manis tersebut dilakukan 20 menit sebelum pemberian makan artemia [41]. Bubuk kayu manis (Cinnamomum verum) merupakan famili Lauraceae yang memiliki efek dalam menurunkan glukosa plasma, dan obesitas [43].…”
Section: Zebrafish Yang Diberi Bubuk Kayu Manisunclassified
“…Berat badan dan indeks massa tubuh pada kelompok yang diberi makan berlebihan menggunakan artemia selama 4 minggu menyebabkan peningkatan berat badan secara signifikan serta obesitas dibandingkan dengan kelompok yang diberi makan normal [40,41]. Pada kelompok makan berlebih yang diberi tambahan kayu manis dengan dosis 6 mg, terjadi penurunan berat badan zebrafish yang signifikan.…”
Section: Zebrafish Yang Diberikan Bubuk Kayu Manisunclassified
See 1 more Smart Citation
“…These changes are too small to be clinically relevant. Animal studies have demonstrated that extracts of cinnamon elicit thermogenesis responses [139], reduced visceral adiposity, attenuated hyperphagia and normalized energy efficiency [140] and attenuated obesity through the modulation of genes implicated in the lipid metabolism pathways [141]. Currently, chronic studies conducted with the cinnamon amount usually consumed in an everyday diet are lacking.…”
Section: Cinnamon Available Evidencementioning
confidence: 99%